2022
DOI: 10.1177/20662203221140646
|View full text |Cite
|
Sign up to set email alerts
|

Identifying mental illness and monitoring mental health in probation service settings

Abstract: There is a need to improve a) identification and monitoring of people with mental illness on probation and b) understanding of the impact of interventions on mental health outcomes for the probation population. If data were routinely collected using validated screening tools and shared between agencies, this could inform practice and commissioning decisions, and ultimately it could improve health outcomes for people under supervision. The literature was reviewed to identify brief screening tools and outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Finally, in Europe, 11% of countries use standardised assessment tools to assess mental health whilst in the US study, 27% reported using a mental health screening tool and 11% reported using a mental health assessment tool. It has been argued in a recent paper published in Europe that probation services should utilise a standardised set of outcomes measures in order to screen the mental health status of all probation clients (Brooker et al, 2022). Overall, it can be concluded that the emphasis on mental illness is far stronger in the US than it is in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in Europe, 11% of countries use standardised assessment tools to assess mental health whilst in the US study, 27% reported using a mental health screening tool and 11% reported using a mental health assessment tool. It has been argued in a recent paper published in Europe that probation services should utilise a standardised set of outcomes measures in order to screen the mental health status of all probation clients (Brooker et al, 2022). Overall, it can be concluded that the emphasis on mental illness is far stronger in the US than it is in Europe.…”
Section: Discussionmentioning
confidence: 99%